2017
DOI: 10.25182/jgp.2017.12.1.41-48
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko Kejadian Berat Badan Lahir Rendah di Area Pertanian (Studi di Kabupaten Brebes)

Abstract: The aim of this study was to analyze the risk factors of Low Birth Weight (LBW) in agricultural area (Breses district) with high pesticide exposure. The research was an observational study with case control design. Study subject were post partum-productive age (20-35 years) ABSTRAKPenelitian ini bertujuan menganalisis faktor risiko kejadian Berat Badan Lahir Rendah (BBLR) di area pertanian (Kabupaten Breses) dengan paparan pestisida yang tinggi. Penelitian ini merupakan penelitian observasional dengan desa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Apart from insufficient information, there are several other factors, such as gestational age, maternal height and weight, lifestyle factors, medical complications during pregnancy, prematurity, poor maternal behavior, maternal anthropometry, socioeconomics, maternal education, household income, and the number of children. or parity (Ratnasari et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from insufficient information, there are several other factors, such as gestational age, maternal height and weight, lifestyle factors, medical complications during pregnancy, prematurity, poor maternal behavior, maternal anthropometry, socioeconomics, maternal education, household income, and the number of children. or parity (Ratnasari et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies reveal that most newborns receive exceptional care in the perinatology room (Hartiningrum & Fitriyah, 2019). One of the factors that cause stress in postpartum mothers is babies born with low birth weight (Ratnasari et al, 2017).…”
Section: Respondents Characteristicmentioning
confidence: 99%
“…The APGAR assessment was carried out one minute 37, and five minutes after the baby was born and was used to determine whether the baby had asphyxia or not. Infants with an APGAR score < 7 within two minutes should be further (Ratnasari et al, 2017). Several factors that can affect the APGAR score are maternal hypoxia, maternal age less than 20 years or more than 35 years, parity, maternal vascular disease, impaired contraction of the mother, placenta (thin, small, not perfectly attached), placental abruption, babies born prematurely, low birth weight, fussy, and disorders of the umbilical cord (Hartiningrum & Fitriyah, 2019).…”
Section: Respondents Characteristicmentioning
confidence: 99%
“…In this study the subjects had experienced weight gain, even though they suffered from nausea and vomiting. Low maternal weight gain, protein intake, and pesticide exposure are the risk factors for low birth weight (LBW) (Ratnasari et al 2017). Another study found that obesity can increased the risk of hyperemesis gravidarum about 50%.…”
Section: Hydration Statusmentioning
confidence: 99%